THE PRIVILEGED COMMUNITIES AND THEIR PARALLEL JUDICATURES IN THE PRE-BRITISH PERIOD IN COCHIN - Kuriakose, Jose (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cochin was a princely state during the British period in India. Cochin became a subsidiary ally of the British in 1791. After this Britain began to control the native society of Cochin through their legal system. Even before the advent of the British, the Jews, Portuguese and the Dutch had different methods of dispute resolution mechanisms based on their own law in Cochin. Different kinds of judicial autonomy were exercised in the legal territory under the Cochin Raja’s jurisdiction. When we consider the legal system of the pre-British period we have to understand the local judicial systems based on cast and religions. Not only is that, it is necessary to understand the early legal system of the Portuguese and the Dutch in Cochin. The pre-British legal system had some similarities in Travancore, Cochin and Malabar. Adjudication in these areas was based on prevailing customs and Maryadas. It was different from religion to religion and caste to caste. Cochin during the colonial period consisted of different communities based on their customs and usages there existed a wide variety of Practices. Immunity was given to Vaniyans and Kongani communities in certain cases. The Brahmin community in the state were also enjoyed some privileges in Cochin in the colonial period. To trace out the evolution of the judicial system of the region of Cochin, it is necessary to understand the early legal immunity enjoyed by these groups in the pre-British Cochin.